THE ROLE OF MECHANOTRANSDUCTION IN OSTEOPOROSIS PATOPHYSIOLOGY - **, Yuliana (Medicina, 2012)
Osteoporosis is o[en encountered by elderly people. It can cause fracture. This disease can be prevented by doing physical activity. Osteocyte as mechanosensory cell, has important role in mechanotransduction system. There are four anabolic transduction signals, i.e. Wnt pathway, BMP/transforming growth factor (TGF)-pathway, ER pathway, and growth hormone/insulin-like growth Factor (IGF)-I pathway. Any disorder on mechanotransduction system will cause osteoporosis.